Dampak Kegiatan Merdeka Belajar Kampus Merdeka (MBKM) Terhadap Kesiapan Memasuki Dunia Kerja pada Mahasiswa S1 Prodi Akuntansi UPN Veteran Jawa Timur - Lilavita Dina Setyawati; Vicky Vendy (Economic Reviews Journal, 2024)
This research aims to examine the impact of the benefits and feedback from supervisors of the Merdeka Belajar Campus Merdeka activities on readiness to enter work among students at the UPN Veteran Jawa Timur. This research is also an evaluation of MBKM activities for the next period. This research was carried out by distributing questionnaires to accounting students 2021 who took part in MSIB and Independent Internships. A total of 91 students filled out the questionnaire out of a total of 340 students. The results of the questionnaire were then analyzed using SEM analysis and SmartPLS 4 software. The results of the SEMPLS analysis showed that the benefits of MBKM had a significant positive impact on students' readiness to enter the world of work, while supervisor feedback had a significant negative impact on students' readiness to enter work. The results of the questionnaire also show that the majority of students agree that the current MBKM implementation partner will become a partner in the next period of MBKM activities